TINGKAT PENGETAHUAN IBU TENTANG DIARE PADA BALITA DI DESA GRINGGING KABUPATEN SRAGEN - Fackrudin Nasrul Sani; Heny Sutanti; Darah Ifalahma (Jurnal Keperawatan Duta Medika, 2021)
Introduction: Diarrhea is a major cause of morbidity and mortality in children worldwide. Diarrhea kills 2 million children in the world every year. Preliminary data in the village of Gringging Village, Sragen Regency, from 10 mothers, 9 mothers had sufficient knowledge, 1 mother did not know about diarrhea. Objective: to find out the Mother's Knowledge Level of Diarrhea in Toddlers in Gringging Village, Sragen Regency. Methods: This type of research is descriptive quantitative. The research sample of mothers who have toddlers in Gringging Village, Sragen Regency, is as many as 33 respondents, using saturated sampling technique. The research instrument used a questionnaire. Data analysis using univariate analysis is presented in the frequency distribution table. Results: The results of this study are the knowledge of mothers about diarrhea in infants in Gringging Village, Sragen Regency, 4 people (12.1%) have good knowledge, 24 people (72.7%) have sufficient knowledge, and 5 people (15.1%) have good knowledge. not enough . Conclusion: In the study of the mother's level of knowledge about diarrhea in toddlers in Gringging Village, Sragen Regency, it can be seen that the majority of respondents have sufficient knowledge.